2021
DOI: 10.3390/cancers13215253
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Gastric Cancer: Identifying Gastric Cancer Using Endoscopic Images with Convolutional Neural Network

Abstract: Gastric cancer (GC) is one of the most newly diagnosed cancers and the fifth leading cause of death globally. Identification of early gastric cancer (EGC) can ensure quick treatment and reduce significant mortality. Therefore, we aimed to conduct a systematic review with a meta-analysis of current literature to evaluate the performance of the CNN model in detecting EGC. We conducted a systematic search in the online databases (e.g., PubMed, Embase, and Web of Science) for all relevant original studies on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Fang et al [ 53 ] revealed the AUC, SEN, and SPE of CNN in the endoscopic image-based GC diagnosis were 0.89, 0.83, and 0.94. Md Mohaimenul Islam et al [ 54 ] revealed that the SROC and SEN of the CNN model in EGC diagnosis were 0.95 and 0.89, respectively. Among the articles included, only 2 articles [ 25 , 26 ] used conventional ML methods (SVM).…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al [ 53 ] revealed the AUC, SEN, and SPE of CNN in the endoscopic image-based GC diagnosis were 0.89, 0.83, and 0.94. Md Mohaimenul Islam et al [ 54 ] revealed that the SROC and SEN of the CNN model in EGC diagnosis were 0.95 and 0.89, respectively. Among the articles included, only 2 articles [ 25 , 26 ] used conventional ML methods (SVM).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CNN has made remarkable progress in the field of endoscopy, including gastrointestinal disorders ( 7 , 8 , 27 31 ). Computer-aided diagnosis studies in upper endoscopy were relatively well established ( 8 , 29 31 ). With derived image data, CNN can facilitate endoscopists with diagnostic and therapeutic interventions by recognizing image features.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the use of artificial intelligence (AI) has reached widespread popularity at an unprecedented rate [ 1 ]. AI algorithms have emerged as potential tools in diverse areas of healthcare, including chronic disease management and clinical decision-making [ 2 , 3 , 4 ]. AI is playing a prominent role in dementia research due to advancements in computing power, novel algorithms, and the availability of big data generated from medical health records and wearable devices [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%